Vitamin K & D Deficiencies Are Independently Associated With COVID-19 Disease Severity. (29th July 2021) - Desai, Ankita P; Dirajlal-Fargo, Sahera; Durieux, Jared C; Tribout, Heather; Labbato, Danielle; McComsey, Grace A
Abstract: Background: We investigated the association of vitamin K and vitamin D with coronavirus disease 2019 (COVID-19) outcomes. Methods: Levels of inactive vitamin K–dependent dephosphorylated uncarboxylated matrix Gla protein (dp-ucMGP; marker of vitamin K status) and 25-hydroxyvitamin D (25(OH)D; vitamin D status) were measured in plasma samples from participants with confirmed acute COVID-19 and were age- and sex-matched to healthy controls. Unadjusted odds ratios and adjusted odds ratios (AORs) with 95% CIs were computed using cumulative logistic regression. Results: One hundred fifty subjects were included, 100 COVID-19+ and 50 controls. The median age (interquartile range) was 55 (48–63) years, and 50% were females. Thirty-four percent had mild COVID-19 disease, 51% moderate disease, and 15% severe. Dp-ucMGP levels were higher (ie, worse K status) in COVID-19+ vs controls (776.5 ng/mL vs 549.8 ng/mL; P < .0001) with similar 25(OH)D between groups (25.8 vs 21.9 ng/mL; P = .09). Participants who were vitamin D deficient (<20 ng/mL) had the worse vitamin K status (dp-ucMGP >780 ng/mL) and experienced the most severe COVID-19 outcomes. In adjusted models, every 1-unit increase in the log2 dp-ucMGP nearly doubled the odds of acute critical disease or death (AOR, 1.84; 95% CI, 1.01–3.45), and every 1-unit decrease in the natural log 25(OH)D was associated with >3 times the likelihood of severe COVID-19 disease (AOR, 0.29; 95% CI, 0.11–0.67). Conclusions: Early in acute COVID-19, both vitamin K and vitamin D deficiency were independently associated with worse COVID-19 disease severity, suggesting a potential synergistic interplay between these 2 vitamins in COVID-19.